Analisis SWOT (Streght, Weakness, Opportunity, Threats) untuk menentukan strategi pemasaran produk pelatihan pada lembaga pelatihan - Sutantio, Erian; Hariastuti, Ni Luh Putu (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT. Indonesia Satu Persada is one of the companies that provides occupational health and safety training and certification. At PT. Indonesia Satu Persada sees that the marketing strategy is less than optimal because the very large market share is not directly proportional to market absorption by PT. Indonesia Satu Persada, therefore it is necessary to conduct an appropriate marketing strategy analysis. The research method used is by using the SWOT method, then an analysis is carried out through efas and ifas to determine the right marketing strategy. After the analysis and calculations were carried out, several activities were obtained that the company needed to do in order to be able to optimize marketing, including conducting new training material topics according to consumer demand, opening cooperation with campuses and providing competitive prices for students, monitoring government regulations related to special training obligations which can then be held at ISP, adding admins and reviewing cooperation with the issuing party of professional certificates in order to be able to carry out administration quickly.